Electronic Government in Mexico - Armenta Bojórquez, Rodolfo Librado (Universidad de Sonora, 2018)
The present research essay describes the subjects that interact in the determination of the Electronic Government in Mexico, as well as their functioning and that paper is the one that takes the Secretariat of the Public Service being responsible for the implementation of the use of Information and Communication Technologies in Mexico. It Is possible that the digital identity card collaborates to better position the country, as it is a tool that can be used in all government areas to expedite the paperwork.